2017
DOI: 10.1016/j.jsps.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Shortage of psychotropic medications in community pharmacies in Saudi Arabia: Causes and solutions

Abstract: Patients with mental disorders, such as depression and anxiety, who seek medical care in private psychiatric clinics in Riyadh, Saudi Arabia, have recently expressed concerns to doctors about difficulty in filling psychotropic medications, such as Amitriptyline and Aripiprazole, at retail community pharmacies. The aim of this study was to investigate whether there is a shortage of some commonly prescribed psychotropic medications in retail community pharmacies in Saudi Arabia, and if so, to explore the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“… 25 The hospitals were categorized into three sectors based on the structure of the Saudi health care system where governmental hospitals differ in their affiliations and sources of funding. 21 The Ministry of Health (MOH) has a separate budget where it funds all hospitals that fall under its authority. Although some medical cities belong to the MOH, they enjoy more autonomous governmental funding channeled through the MOH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 The hospitals were categorized into three sectors based on the structure of the Saudi health care system where governmental hospitals differ in their affiliations and sources of funding. 21 The Ministry of Health (MOH) has a separate budget where it funds all hospitals that fall under its authority. Although some medical cities belong to the MOH, they enjoy more autonomous governmental funding channeled through the MOH.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that explored the scarcity of commonly prescribed psychotropic drugs, almost 50% of more than 240 community pharmacies in different regions in Saudi Arabia reported drug shortages. 21 Although drug shortages represent a significant global issue to many healthcare systems, there is a dearth of studies on the prevalence and causes in Saudi Arabia. 19 22 …”
mentioning
confidence: 99%
“…[16] In addition, the author found that the essential medications were missing at the community pharmacy. [15] The missing medications and lack of follow-up consequently affected patient's management care.…”
Section: Assessment Needsmentioning
confidence: 99%
“…[7,[13][14] whereas studies regarding the status of stock inventory at the pharmacy in Saudi Arabia are scarce. [15][16] This might be because of the unclear inventory management system at the MOH institutions. The general administration of pharmaceutical care at MOH started initiative steps and established pharmacy inventory system for pharmacy in healthcare institutions including hospital or specialized centers or primary healthcare centers or dental ambulatory care clinics.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Despite that, still there is shortage of medication at outside and inside Saudi Arabia. [7][8][9] Several studies conducted to measure the actual situation of the pharmacy inventory management system of medications at hospital pharmacies. [10][11][12] Also, the famous studies of pharmacy practice through American Society of Health-system pharmacist did not cover pharmacy stock management very well.…”
Section: Introductionmentioning
confidence: 99%